EFFECT OF PLANT DENSITY AND FOLIAR NUTRITION OF SEAWEED ON SOME CHARACTERISTICS OF VEGETATIVE GROWTH OF FOUR VARIETIES OF KOHLRABI CROP - Al-Shammsri, Aziz Mahdi; Alalawy , Hassan H.; Hathal, Ayad Ahmed (Diyala Agricultural Sciences Journal, 2020)
The field experiment was conducted at the research station of the Department of Horticulture and Gardening Engineering at the College of Agriculture Diyala University in the agricultural season 2018 and the study included the response of four varieties of Kohlrabi, namely green delicacy and local and purple delicacy and Vienna White for cultivation with two plant densities first 53333 plants H-1 and the second 106666 plants H-1 Foliar feeding has three levels of marine algae extract for valgren 0, 3, and 6 mL -1 . A global experiment was carried out within the splitsplinter system within the complete randomized sector design, as densities were placed in the main plates and the foliar feeding levels were extracted with seaweed extract in the secondary plates, while the plant varieties were placed in subsecondary units, the data of the studied traits were recorded and their averages were compared with the polynomial Duncan test At the probability level 0.05. The study showed significant differences between the varieties, as the green delicacy variety outperformed the number of leaves, while the purple delicacy variety outperformed the total chlorophyll content and the percentage of dry matter in the leaves, while the local variety and purple delicacy excelled in plant height and leaf length. Plants cultivated with the first density were significantly superior in leaf length, foliar area and percentage of dry matter in the leaves compared to plants cultivated with the second density. There were no significant differences between the two densities in plant height, number of leaves and total chlorophyll. The fertilizing treatment with vulgene algae at a concentration of 6 mL -1 was significantly higher in plant height, number of leaves, leaf length, leaf area and total chlorophyll compared to the treatment without spraying. Triangular interference had a significant effect on all traits. The treatment of the cultivar of the purple delicacy cultivated in the first density and fertilized with a concentration of 6 ml-1 of the felgae was significantly superior in the leafy area, the total chlorophyll and the percentage of the dry matter in the leaves, while the treatment of the green delicacy cultivar in the The first density of fertilizer with a concentration of 6 ml -1 liter was significant in number of leaves.